ALRIGHT: A DISTINCTIVE PATHWAY OF CHANGE FROM THE 18TH CENTURY TO THE PRESENT DAY - Ruiz, Pedro (2019)
The origins of the vast majority of the words we use in contemporary English go back as far as Old or Middle English. In contrast, alright and all right in their present-day application appear to be the result of a more recent evolution, as there is no evidence of their use, not even in the two-word form, in the published fiction before the 18th century. Furthermore, there are not in the research literature, at least to my knowledge, any previous linguistic studies on this specific subject matter. The present article is simply an attempt to describe the various processes of diachronic change that brought about the emergence of alright.